2008
DOI: 10.1021/ja807888k
|View full text |Cite
|
Sign up to set email alerts
|

Stable Scaffolds for Reacting Si Nanowires with Further Organic Functionalities while Preserving Si−C Passivation of Surface Sites

Abstract: Silicon nanowires (Si NWs) represent an attractive class of building blocks for nanoelectronics and sensors. However, for many applications, the presence of oxide on the Si NW surface is undesirable, because a defective oxide layer (e.g., native SiO 2 ) induces uncontrolled interface states in the band gap of the Si.Freshly prepared H-terminated Si NWs have low surface recombination velocities but are not stable in air for more than a few hours, because disordered oxide layers form.1 Recently, we have reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(90 citation statements)
references
References 10 publications
2
88
0
Order By: Relevance
“…25 To this end, the H-terminated Si surfaces of both single-crystal and porous Si substrates have been alkylated using alkylmagnesium reagents, 5,[26][27][28] and halogenated surfaces have been alkylated using alkylmagnesium or alkyllithium reagents. 29 Alkylation has also been accomplished through free-radical initiation methods such as irradiating with ultraviolet light, 30,31 chemical free-radical activation, 32,33 thermal activation, 34,35 Lewis acid catalyzed hydrosilylation, 36,37 or visible-light-initiated modification of H-Si at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…25 To this end, the H-terminated Si surfaces of both single-crystal and porous Si substrates have been alkylated using alkylmagnesium reagents, 5,[26][27][28] and halogenated surfaces have been alkylated using alkylmagnesium or alkyllithium reagents. 29 Alkylation has also been accomplished through free-radical initiation methods such as irradiating with ultraviolet light, 30,31 chemical free-radical activation, 32,33 thermal activation, 34,35 Lewis acid catalyzed hydrosilylation, 36,37 or visible-light-initiated modification of H-Si at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 7 shows the JvsV characteristics across the RNpropenyl-SiNWs/n-Si after a subsequent covalent attachment at propenyl-SiNWs of TDBA for two different illumination time of a 365 nm broadband UV lamp [15,16]. It can be observed that the carrier transport across the propenyl-SiNWs/nSi junction is strongly affected by TDBA covalent attachment and is represented by a large increase of forward current level and rectification.…”
Section: Resultsmentioning
confidence: 99%
“…After immersion for 2 h, the samples were cleaned by rinsing with DMF and CH2Cl2, and dried by N2(g) flushing. [15,16] Figure 1(a-b) displays a typical top view (1a) and cross sectional scanning electron micrograph (1b) of a SiNWs random network fabricated on the n-Si substrate. The average SiNWs length, roughly corresponding to the thickness of the SiNWs random network, was estimated around 2 m, while the single SiNW had an estimated average diameter of 50 nm.…”
Section: Si Nws Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…14−16 However, such modification approach would bring about the inhomogeneity and variability in the number of Si−O−Si and Si−OH linkages, which could affect the consistency of the SiNWs-based devices. 8 In order to improve the controllability of the SiNWs-based devices, two-step amine-promoted reaction procedure has been used to passivate most of the SiO 2 /SiNW surface trap states by appropriate monolayers. 9 An alternative way is to remove the native oxide layer by hydrofluoric acid (HF) and the resultant Si−H bonds dominating the surface of the SiNWs could be utilized to functionalize the SiNWs.…”
Section: Introductionmentioning
confidence: 99%